Semi-Quantification of Total Campylobacter and Salmonella During Egg Incubations Using a Combination of 16S rDNA and Specific Pathogen Primers for qPCR - Rothrock, Michael J.; Feye, Kristina M.; Kim, Sun Ae; Park, Si Hong; Locatelli, Aude; Hiett, Kelli L.; Gamble, John; Sellers, Holly; Ricke, Steven C. (Frontiers in Microbiology, 2018)
Rapid molecular techniques that evaluate eggs for the presence of foodborne pathogens is an essential component to poultry food safety monitoring. Interestingly, it is not just table eggs that contribute to outbreaks of foodborne disease. Broiler layer production actively contributes to sustaining of foodborne pathogens within a flock. The surface contamination of production eggs with invasive pathogens such as Salmonella enterica, Campylobacter jejuni, and Listeria monocytogenes during embryogenesis results in gastrointestinal tract (GIT) colonization. Pathogens that secure a niche within the GIT during embryonic development are nearly impossible to eradicate from the food chain. Therefore, current monitoring paradigms are not comprehensive because they fail to capture the presence of invasive pathogens within the embryonic GIT rapidly. By developing tools to recognize the pathogens’ presence in the GIT during embryogenesis, producers are then able to spot evaluate broiler eggs for their potential risk as carriers of foodborne pathogens. In this study a novel qPCR assay was developed to semi-quantify pathogen load relative to total bacterial burden. Eggs sampled from three independent production broiler flocks of different ages were assayed for Salmonella enterica (invA), Campylobacter jejuni (HipO), and Listeria monocytogenes (HlyA) against total microbial load (16s). The eggs were sampled at one-day post-set within each flock, two weeks post-set, after vaccination (at 2.5 weeks) and one-day post-hatch. The eggs were washed, and the yolk and embryonic chick GIT were collected. The DNA was extracted and subjected to a qPCR assay. The results confirm a novel technique for pathogen monitoring relative to total bacterial load and a unique method for monitoring the dynamics of foodborne pathogen invasion throughout broiler egg production.